Determinant of Desire to Commit Fraud in the Procurement of Goods/Services Within State Universities - Ummi Kalsum (Green Publisher Indonesia, 2021)
The purpose of this study was to examine whether the variables of the quality of the goods / services procurement committee, quality of providers, procurement environment, risk assessment and systems and procedures had an influence on the desire to commit fraud in the procurement of goods / services at state universities in Yogyakarta. This research uses quantitative methods with primary data collected from the survey method of commitment-making officials (PPK), procurement committees, and committees / officials receiving work results at state universities in Yogyakarta. The sample in this study came from 65 respondents from nine state universities and were selected using purposive sampling. The analysis technique used in this study is multiple linear regression analysis using SPSS software. The results of data analysis indicate that the procurement environment and procurement systems and procedures have a positive and significant effect on the desire to commit fraud in the procurement of goods / services. Meanwhile, the quality of the procurement committee, the quality of the providers, and the risk assessment did not affect the desire to commit procurement fraud at public universities in Yogyakarta. From the results of research and discussion, it can be concluded that the better or the worse the level of the procurement environment/ internal environment and the systems and procedures at state universities have an effect on the high and low levels of things that trigger the desire to commit fraud in the procurement of goods/ services.